Effects of Ganoderma lucidum polysaccharide peptide ameliorating cyclophosphamide-induced immune dysfunctions based on metabolomics analysis - Xie, Jing; Lin, Dongmei; Li, Jing; Zhou, Tonghui; Lin, Shuqian; Lin, Zhanxi (Frontiers in Nutrition, 2023)
Ganoderma lucidum polysaccharide peptide (GLPP), is one of the most constituents of Ganoderma lucidum (G. lucidum) with a wide range of functional activities. The present study investigated the immunomodulatory effects of GLPP in cyclophosphamide(CTX)-induced immunosuppressive mice. The results showed that 100 mg/Kg/d of GLPP administration remarkably alleviated CTX-induced immune damage through improving immune organ indexes, earlap swelling rate, the index of carbon phagocytosis and clearance value, secretion of cytokines (TNF-α, IFN-γ, IL-2), and immunoglobulin A(IgA) in the mice. Furthermore, ultra performance liquid chromatography of mass/mass spectrometry (UPLC-MS/MS) was performed to identify the metabolites, followed by biomarker and pathway analysis. The results showed that GLPP treatment alleviated CTX-induced alterations in the fecal metabolome profile, including arachidonic acid(AA),leukotriene D4(LTD4), indole-3-ethanol, formyltetrahydrofolate(CF), by reversing citric acid, malic acid, cortisol , and oleic acid. These results support the concept that GLPP exhibit immunomodulatory activity via folate cycle, methionine cycle, TCA cycle, fatty acid biosynthesis and metabolism, glycerophospholipid metabolism, AA metabolism and cAMP pathways. In conclusion, the results could be helpful to GLPP to clarify the immunomodulatory mechanism ,and be used as immunostimulants to prevent CTX-induced side effects in immune system.